Aluminum fluoride-18 labeled folate enables in vivo detection of atherosclerotic plaque inflammation by positron emission tomography - Johanna M. U. Silvola; Xiang-Guo Li; Jenni Virta; Päivi Marjamäki; Heidi Liljenbäck; Jarkko P. Hytönen; Miikka Tarkia; Virva Saunavaara; Saija Hurme; Senthil Palani; Harri Hakovirta; Seppo Ylä-Herttuala; et al. (NATURE PUBLISHING GROUP, 2025)
Inflammation plays an important role in the development of atherosclerosis and its complications. Because the folate receptor beta (FR-beta) is selectively expressed on macrophages, an FR targeted imaging agent could be useful for assessment of atherosclerotic inflammation. We investigated aluminum fluoride-18-labeled 1,4,7-triazacyclononane-1,4,7-triacetic acid conjugated folate (F-18-FOL) for the detection of atherosclerotic plaque inflammation. We studied atherosclerotic plaques in mice, rabbits, and human tissue samples using F-18-FOL positron emission tomography/computed tomography (PET/CT). Compound 2-deoxy-2-[F-18]fluoro-D-glucose (F-1(8)-FDG) was used as a comparison. Firstly, we found that the in vitro binding of F-18-FOL co-localized with FR-beta-positive macrophages in carotid endarterectomy samples from patients with recent ischemic symptoms. We then demonstrated specific accumulation of intravenously administered F-18-FOL in atherosclerotic plaques in mice and rabbits using PET/CT. We noticed that the F-18-FOL uptake correlated with the density of macrophages in plaques and provided a target-to-background ratio as high as F-18-FDG, but with considerably lower myocardial uptake. Thus, F-18-FOL PET/CT targeting of FR-beta-positive macrophages presents a promising new tool for the in vivo imaging of atherosclerotic inflammation.